Use of Intrinsic Capacity Domains as a Screening Tool in Public Health - Nascimento, Livia Maria do [UNESP]; Cruz, Thainá Gabriele Camargo da [UNESP]; Silva, Juliana Fernanda de Lima e [UNESP]; Silva, Letícia Prado [UNESP]; Inácio, Beatriz Bigatão [UNESP]; Sadamitsu, Carolina Masumi Oki [UNESP]; Scheicher, Marcos Eduardo [UNESP] (MDPI, 2023)
The World Health Organization (WHO) created the concept of Integrated Care for Older People and one of its constructs is intrinsic capacity (IC). The study aimed to carry out a screening with the tools designated by the WHO to assess the IC domains and whether they can be used as indicators for decision-making on integrated care for older people based on risk categorization. The interaction between the risk category and the domain scores was verified. One hundred and sixty three (163) community-dwelling older people of both genders were evaluated. Domains assessed: cognitive, psychological, vitality, locomotion, and sensory. Scores indicating a low, moderate and high risk were assigned to each domain. For all domains, there were individuals in all risk groups. Effect of risk on the domains: cognitive [χ2(2) = 134.042; p < 0.001], psychological [χ2(2) = 92.865; p < 0.001], vitality [χ2(2) = 129.564; p < 0.001], locomotion [χ2(2) = 144.101; p < 0.001], and sensory [χ2(2) = 129.037; p < 0.001]. Scores of the CI domains were affected by the risk category. There were individuals in all risk groups, demonstrating the importance of screening as a public health strategy, making it possible to know which risk category each elderly person belongs to and thus develop strategies in the short-, medium- and long-term.
Keywords: aging; intrinsic capacity; screening tests